Accidents in Malawi. Issue 1 (January 1985) - Simmons, D
Abstract : The frequency and types of children's accidents during a two month period in Malawi are described, showing that these are at least as numerous as in developed countries. It is suggested that preventive measures and an improvement in immediate treatment are required.